2021
DOI: 10.1029/2020jd033338
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Cloud Processing for the Ice Nucleating Ability of Organic Aerosol and Coal Fly Ash Particles

Abstract: • Cloud processing can increase organic particle viscosity enhancing their ice nucleation activity 10 • Coal fly ash particles show a decreased ice nucleation ability after cloud process-11 ing 12 • Aerosol generation methods impact the observed ice nucleation abilities of coal 13 fly ash particles 14

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 93 publications
(280 reference statements)
0
10
0
Order By: Relevance
“…These observations suggest that the changes with time in absorptivity of secondary BrC from phenolic precursors are greater than the changes in hygroscopicity. It is noted that cloud droplet activation at supersaturation 24 as well as ice nucleating ability 98 will influence the relative contributions of the direct and indirect effects, so this will need to be explored to complete the understanding of cloud processing of phenolic precursors.…”
Section: ■ Introductionmentioning
confidence: 99%
“…These observations suggest that the changes with time in absorptivity of secondary BrC from phenolic precursors are greater than the changes in hygroscopicity. It is noted that cloud droplet activation at supersaturation 24 as well as ice nucleating ability 98 will influence the relative contributions of the direct and indirect effects, so this will need to be explored to complete the understanding of cloud processing of phenolic precursors.…”
Section: ■ Introductionmentioning
confidence: 99%
“…We observed the evidence of OA acting as immersion freezing INPs at a temperature warmer than that reported in other studies, for instance, isoprene initialized secondary organic aerosol (SOA) was found to nucleate at temperatures <−30°C in the laboratory (Ignatius et al., 2016; Ladino et al., 2014), and naphthalene‐induced SOA, a surrogate of anthropogenic SOA types, showed higher ice nucleating efficiency than biogenic SOA (Charnawskas et al., 2017). Further, recent studies have suggested that the phase state is a key factor in determining the contribution of OA to INPs (Kilchhofer et al., 2021; Wagner et al., 2015, 2017). Biogenic SOA was previously reported to not show a glass transition, which is shown by anthropogenic SOA (Liu et al., 2016), indicating that the latter may be more likely to be solid under low RH and serve as INPs.…”
Section: Resultsmentioning
confidence: 99%
“…Deposition ice nucleation requires low ice supersaturation and temperature values which exclude haze particle or liquid droplet formation and homogeneous freezing. In addition to molecular composition, the trajectory of the particle along a thermodynamic path, and the glass transition temperature ( T g ), which is non‐equilibrium phase transition temperature from glassy solid‐phase to semi‐solid phase (Koop et al., 2011), are important modulators of the ice nucleating ability of a particle (e.g., Berkemeier et al., 2014; Charnawskas et al., 2017; Kilchhofer et al., 2021; Lienhard et al., 2015; Murray et al., 2010). When the glassy particle is exposed to an increase of RH, it starts to liquefy and form a core‐shell morphology then the water diffuses into the glassy matrix.…”
Section: Introductionmentioning
confidence: 99%
“…Many model organic species have been identified as IN active substances (Baustian et al., 2013; Gavish et al., 1990; Kilchhofer et al., 2021; Knopf et al., 2018; Murray et al., 2010; Rosinski et al., 1990; Wagner et al., 2010; Wolf et al., 2020). The reported observations show that particles composed of pure organic compounds such as sucrose (Baustian et al., 2013), raffinose (Kilchhofer et al., 2021; Wagner et al., 2012; Wilson et al., 2012), citric acid (Murray et al., 2010), and oxalic acid dihydrate (Wagner et al., 2010) nucleate ice in the heterogeneous regime. Deposition ice nucleation requires low ice supersaturation and temperature values which exclude haze particle or liquid droplet formation and homogeneous freezing.…”
Section: Introductionmentioning
confidence: 99%